Fewer in number but harder to employ: Incidence and duration of unemployment in an economic upswing - Erik Hernæs (University of Oslo, Department of Economics, 1999)
During the upswing in the Norwegian labour market after the peak of unemployment in the post-war period in the early 1990s, the inflow to unemployment fell by one fourth from October 1991 to October 1993. In contrast, the expected unemployment duration remained fairly constant, whether measured by the duration of registered unemployment or by the duration of joblessness. The continued high duration of unemployment was partly due to a decrease in average `employability' in the unemployment inflow: more immigrants from non-western countries, more without job experience, more with previous unemployment experience, lower average previous earnings, and fewer on recall notice.
Keywords: 330; Arbeitslosigkeit; Dauer; Arbeitsmarkt; Norwegen